THE INFLUENCE OF MARKET ORIENTATION ON BUSINESS PERFORMANCE OF MICRO SMALL ENTERPRISES OF TEMPE - Rosiana, Agista (Jurnal Pertanian, 2020)
Market orientation is one of the business culture that produces the best performance through commitment to the customer. The aim of study is to analyze the factors that affect market orientation in operate a business to improve business performance on MSEs in the city of Bogor. The research was conducted on micro small business of tempe in Bogor City. The number of respondents in the research as much as thirty respondents with the determination of respondents by purposive sampling. Data analysis using Structural Equation Modeling (SEM) analysis with smart partial least squares (smart PLS) approach. The results of this study indicated customer orientation variables significantly affect business performance with the results of T tests 2.996> 1.96, competitor orientation variables significantly affect business performance with the test results T 2.544> 1.96, and variables interfunctional coordination was not significantly affect business performance with test results T 1.687 <1.96. Thus, customer orientation and competitor orientation have significant influence to business performance, while inter-functional coordination factor not give significant influence to business performance. Keywords : Market Orientation, Partial Least Square